PENGARUH BELANJA FUNGSI PENDIDIKAN, BELANJA FUNGSI KESEHATAN DAN PENGANGGURAN TERHADAP KEMISKINAN DALAM PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) DI PROVINSI SUMATERA BARAT - Sri Rahma Witta; Anna Yulianita; Alghifari Mahdi Igamo; Imelda Imelda (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2022)
This study aimed to analyze the effect of spending on education functions, spending on health functions and unemployment on poverty in achieving Sustainable Development Goals (SDGs) in West Sumatra Province. The data used in this study was panel data consisting of cross section data, data of 19 districts/cities in West Sumatra Province and time series data, data from 2016 to 2020. The analysis technique used is multiple linear regression of panel data with Fixed Effect Model approach. The results showed that education function expenditure had a positive effect and significant with a coefficient of 0.048088, health function expenditure had a negative effect and significant with a coefficient of -0.095445, while unemployment had a positive effect and not significant with a coefficient of 0.001206 on poverty in achieving Sustainable Development Goals (SDGs) of districts/cities in West Sumatra Province in 2016-2020.